2015
DOI: 10.3109/02699052.2015.1015613
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions profiles in traumatic brain injury adults: Implications for rehabilitation studies

Abstract: The first cluster replicated findings of previous studies on TBI EF profiles. IT is suggested that TBI rehabilitation studies of EF must select participants by their EF profile rather than for clinical or demographical variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…There was also no significant influence of working memory or executive function ability on overall BGT performance, which is in keeping with some previous studies (e.g., Bechara et al, 1998; Turnbull et al, 2005). It is worth noting that there was also no significant difference between the survivors of TBI and controls on these measures which, although inconsistent with some studies of neurocognitive performance following TBI (e.g., Dunning, Westgate, & Adlam, 2016; Zimmermann et al, 2015), is consistent with findings reported in patients with anterior VMPfC (i.e., poorer emotion-based decision making relative to controls but intact working memory, Bechara et al, 1998).…”
Section: Discussionmentioning
confidence: 53%
“…There was also no significant influence of working memory or executive function ability on overall BGT performance, which is in keeping with some previous studies (e.g., Bechara et al, 1998; Turnbull et al, 2005). It is worth noting that there was also no significant difference between the survivors of TBI and controls on these measures which, although inconsistent with some studies of neurocognitive performance following TBI (e.g., Dunning, Westgate, & Adlam, 2016; Zimmermann et al, 2015), is consistent with findings reported in patients with anterior VMPfC (i.e., poorer emotion-based decision making relative to controls but intact working memory, Bechara et al, 1998).…”
Section: Discussionmentioning
confidence: 53%
“…An epidemic that affects mainly the young damages a country's future. 9 From 11 studies, 1,5,6,8,[10][11][12][13][14][15][16] car accidents were involved in 43% of TBI, as compared with motorbike (30%) and pedestrian (27%). Of the six studies 1,6,11,12,14,15 (n = 1,753) including a pedal bicycles category, car dropped slightly to 40%, while motorbike and pedestrian were both associated with 23% of TBI and pedal bike was related in 14% of TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Cluster analysis has been extensively applied in the study of TBI in the last 30 years [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Nevertheless, we have identified several common limitations such as the number of TBI patients that were clustered (<100 in many studies), the clustering approaches (only hierarchical clustering and k-means and not discussing other possible techniques), the specific implementation of such techniques (most of them restricted to only commercial products), as well as the lack of relation between the obtained clusters and rehabilitation tasks.…”
Section: Clustering In Tbimentioning
confidence: 99%
“…We have worked with public GNU libraries, as opposed to the state-of-the-art publications presented in Table A1, wherein most techniques were implemented using commercial packages [15][16][17][18][20][21][22][23][25][26][27][29][30][31]. Previous research presented in Table A1 applied clustering techniques in a batch mode as desktop applications.…”
Section: Comparison With Prior Workmentioning
confidence: 99%